Tillering and morphological characteristics of dwarf elephantgrass under grazing - Rodrigues, Luis Roberto de A.; Mott, Geraldo O.; Veiga, Jonas B.; Ocumpaugh, William R. (Pesquisa Agropecuaria Brasileira, 2014)
Morphological characteristics and tillering of dwarf elephantgrass (Pennisetum purpureum Schum.) were studied in a grazing trial conducted at the University at Florida - USA. The grass was subjected to the effects of two management factors, each at five levels as follows: length of grazing cycle (GC) (continuous grazing, 14, 28, 42 and 56 days) and grazing pressure (GP) (500, 1,000, 1,500, 2,000 and 2,500 kg at residual leaf dry matter ha-1). Response surface methodology was used to analyse the data. Increases in GC and decreases in GP increased plant height, apical meristems height, number of internodes and dry matter produced per tiller. The percentage of apical meristems eliminated was greater under continuous grazing and high GP. The number of axillary buds per tiller was depressed under high GP. Shorter internodes were observed at short GC and high GP. Primary tillers constituted the predominant from of tillering in this grass. The results obtained indicate that short grazing cycles and high grazing pressures should be avoided in the management of dwarf elephantgrass in order to insure persistence and productivity of the pasture.
Keywords: Pennisetum purpureum; grazing trial; pasture management; management factors